Scheduling in Bag-of-Task grids: the PAUA case - Cirne, W.; Brasileiro, F.; Costa, L.; Paranhos, D.; Santos-Neto, E.; Andrade, N.; Rose, C. De; Ferreto, T.; Mowbray, M.; Scheer, R.; Jornada, J. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
In this paper we discuss the difficulties involved in the scheduling of applications on computational grids. We highlight two main sources of difficulties: 1) the size of the grid rules out the possibility of using a centralized scheduler; 2) since resources are managed by different parties, the scheduler must consider several different policies. Thus, we argue that scheduling applications on a grid require the orchestration of several schedulers, with possibly conflicting goals. We discuss how we have addressed this issue in the context of PAUA, a grid for Bag-of-Tasks applications (i.e. parallel applications whose tasks are independent) that we are currently deploying throughout Brazil.